COUNTRIES WITHOUT OWNING RAILWAY TRANSPORT - M.N. Kamolov (International Scientific and Current Research Conferences, 2022)
The article discusses the countries of the world that do not have railway transport, the railway transport system, land transport, the first railway transport, the history of railway transport in Uzbekistan.